Pengembangan Bahan Ajar Inovatif Berbasis Multimedia Untuk Meningkatkan Hasil Belajar Mahasiswa Pada Pembelajaran pH Larutan - Lisa Ariyanti Pohan; Manihar Situmorang; Iis Siti Jahro (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. This study was aimed to obtain innovative teaching material based on multimedia to learning the pH solution which can improve learning outcomes and student motivation. The population of this research was all of the even semester students of the State University of Medan (UNIMED). The research sample was taken by using the purposive random samplingwith ± 76 students as the samples who were studying General Chemistry II course at the UNIMED consisting of two classes, the experimental class and the control class. The experiment class used innovative teaching materials that have been developed while the control class used the chemistry student handbook. Five lecturers from the UNIMED and the North Sumatera Islamic University (UISU) were appointed as the validators of the developed innovative teaching materials. The results showed that: (1) the chemistry books that were analyzed gave an average 49,67% which is considered adequate and do not need any revision. However,there are some shortcomings in each book that needs to be developed, (2) the components which are integrated into the developed innovative teaching materials were the integration of the learning model and methods, laboratory activities, campus outside activities, the video and animation multimedia learning materials created using the flip book maker software, (3) the assessment results from the expert validator toward the developed innovative teaching materials is 4,35 which is considered valid and do not need any revision, while the assessment result from the multimedia lecturers 4,4 which is considered valid and do not need any revision, (4) the student learning outcomes that used the innovative teaching materials based on multimedia in learning pH solution is higher than the outcomes of the students who used the student handbook with tcount >ttable (4,70 > 1,99), (5) the effectiveness of applying the innovative teaching materials based on multimedia in learning the pH solution showed the student learning outcomes improved to 78%, and (6) the students gave positive feedback and response to the innovative teaching materials based on multimedia in learning pH solution with the average acquisition value 4,05 which means that it is proper to use. Keyword: teaching materials, innovative, multimedia, learning outcomes, pH of  the solution